Derivation of an Accurate Force-Field for Simulating the Growth of Calcium Carbonate from Aqueous Solution: A New Model for the Calcite-Water Interface - Raiteri, Paolo; Gale, Julian; Quigley, D; Rodger, P (American Chemical Society, 2010)
The performance of existing force-field models for the calcium carbonate - water system has been critically assessed with particular reference to the thermodynamic consequences. It is demonstrated that all currently available parametrizations fail to describe the calcite-aragonite phase transition, and the free energies of solvation for the calcium cation are also considerably in error leading to a poor description of the dissolution enthalpy for calcite. A new force-field, based on rigid carbonate ions, has been developed that corrects these deficiencies and accurately describes the thermodynamics of the aqueous calcium carbonate system within molecular dynamics simulations. Not only does this new model lead to quantitative changes in the properties of the calcite (101j4) surface in contact with water, but also significant qualitative differences. With this more accurate model it is found that calcium ions do not adsorb at the pristine basal plane of calcite, while carbonate ions only weakly bind. Carbonate diffusion across the surface is found to occur only when the anion is solvent separated from the underlying surface, with there being an equal tendency to readsorb or migrate into the bulk liquid.